Application Progress of Organoids in Colorectal Cancer - Luo, Lianxiang; Ma, Yucui; Zheng, Yilin; Su, Jiating; Huang, Guoxin (Frontiers in Cell and Developmental Biology, 2022)
Currently, colorectal cancer is still the third leading cause of cancer-related mortality, and the incidence is rising. For a long time, the models of colorectal cancer research have always used cell lines and animals, however, these models are different from the human body. Organoids have more clinical significance than cell lines, and it also bridge the gap between animal models and human body. Patient derived organoids are three-dimensional cultures that simulate the tumor characteristics in vivo, recapitulate tumor cell heterogeneity. Therefore, the emergence of colorectal cancer organoids provides an unprecedented opportunity for colorectal cancer research. It retains the molecular and cellular composition of the original tumor, and has a high degree of homology and complexity with patient tissues. Patient-derived colorectal cancer organoids, as personalized tumor organoids, which can more accurately simulate the occurrence, development, metastasis of colorectal cancer and predict the drug response of patients. Colorectal cancer organoids show great potential for application, especially preclinical drug screening and prediction of patient response to selected treatment options. In this review, we reviewed the application of colorectal cancer organoids in disease model construction, basic biological research, organoid biobank construction, drug screening and personalized medicine, drug development, drug toxicity and safety, and regenerative medicine. In addition, we also explore the current limitations and challenges of organoids, and discuss the future development direction of organoids in combination with other technologies. Combination with other advanced technologies, the future development direction of organoids is discussed. Finally, we summarized and analyzed the current clinical trial research of organoids, especially the clinical trials of colorectal cancer organoids, and clarified the current research content of colorectal cancer organoids, we hope to lay a solid foundation for future colorectal cancer organoid research.